2021
DOI: 10.1166/jon.2021.1782
|View full text |Cite
|
Sign up to set email alerts
|

Buoyant Convective Flow and Heat Dissipation of Cu–H2O Nanoliquids in an Annulus Through a Thin Baffle

Abstract: This article numerically investigates the buoyant convective flow and thermal transport enhancement of Cu–H2O nanoliquid in a differentially heated upright annulus having a thin baffle. For the analysis, the outer and inner cylinders are cooled and heated respectively through insulated top and lower boundaries. Also, the baffle temperature is assumed to be that of the hot cylinder. The finite difference based numerical technique is used to solve the system of equations governing the physical processes. The fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(16 citation statements)
references
References 50 publications
0
16
0
Order By: Relevance
“…Over the years, numerous researchers have investigated the optical absorption and photothermal conversion properties of these nanofluids. Studies on metallic [63,64], metal oxide [65,66], carbides, nitrides, graphene, A c c e p t e d M a n u s c r i p t graphite, and carbon nanotube nanoparticle-based monocomponent nanofluids have been identified and discussed. Significant findings from studies on optical property characterization of nanofluids have been summarized in Table 1.…”
Section: Monocomponent Nanofluids For Dascsmentioning
confidence: 99%
“…Over the years, numerous researchers have investigated the optical absorption and photothermal conversion properties of these nanofluids. Studies on metallic [63,64], metal oxide [65,66], carbides, nitrides, graphene, A c c e p t e d M a n u s c r i p t graphite, and carbon nanotube nanoparticle-based monocomponent nanofluids have been identified and discussed. Significant findings from studies on optical property characterization of nanofluids have been summarized in Table 1.…”
Section: Monocomponent Nanofluids For Dascsmentioning
confidence: 99%
“…Other authors [44,45] studied convective flow inside enclosures with different hot-shaped inner cylinders. Several other references were utilized to establish this work [46][47][48][49][50][51].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was showed that the curved corners have a significant influence on the flow structure and energy consumption. On the other hand, the considerable impacts of nanofluid on the natural convection (Pushpa et al , 2021), entropy generation (Mebarek-Oudina et al , 2021), heat transfer rate (Marzougui et al , 2021; Shafiq et al , 2021) have been proven by the researchers. Swain et al (2021) investigated the influence of chemical reaction and variable magnetic field of MWCNT/Fe 3 O 4 –water nanofluid in a shrinking porous sheet.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it was showed that the curved corners have a significant influence on the flow structure and energy consumption. On the other hand, the considerable impacts of nanofluid on the natural convection (Pushpa et al, 2021), entropy generation (Mebarek-Oudina et al, 2021), heat transfer rate (Marzougui et al, 2021;Shafiq et al, 2021) The natural convection problem in a thermal storage is analyzed using numerical and experimental approaches. The Bhatnagar-Gross-Krook (BGK) lattice Boltzmann method is used for the numerical simulations, and experimental measurements are conducted for thermos-physical properties of Al 2 O 3 -oil nanolubricant.…”
Section: Introductionmentioning
confidence: 99%